Breast Cancer Mortality in Young Women in Brazil - Silva, Juliana Dalcin Donini E.; de Oliveira, Rosana Rosseto; da Silva, Mariana Teixeira; Carvalho, Maria Dalva de Barros; Pedroso, Raissa Bocchi; Pelloso, Sandra Marisa (Frontiers in Oncology, 2021)
Objective: Malignant breast cancer is the leading cause of cancer death in young women. The study aimed to describe the breast cancer mortality trend of Brazilian young women and correlate it with socioeconomic variables to propose the inclusion of these women in screening programs. Methods: A time-series analysis of breast cancer mortality rate in young women (20-39) was carried out. Mortality data, from 1996 to 2017, were collected from the Mortality Information System of the Health Ministry and demographic data from the Brazilian Institute of Geography and Statistics. Trends in mortality were performed by Joinpoint regression, the spatial distribution of the mortality rate was done with QGIZ Software version 2.18, and Spearman’s correlation coefficient was used to correlate the mortality rates with the Human Development Index. Results: There was an increase in breast cancer mortality rates in young women in most Brazilian states, with an upward trend in all regions. The correlation with the Municipal Human Development Index, income, and education had a significant impact on the mortality rate for women from 30-39 years in both periods evaluated and for women from 20-29, only from 1996 to 2000. Conclusion: The data obtained in the study, demonstrated that even though the mortality rate of young women is lower than women over 40 years, it has been increasing in all regions of Brazil, mainly for women from 30-39 years, suggesting that this group could be included in screening programs.